FEATURES OF IMMUNE CELLS IN ACUTE LYMPHOBLASTIC LEUKEMIA - O. V. Smirnova (SPb RAACI, 2014)
Abstract. In this study, we have identified functional features of immune system cells in patients with acute lymphoblastic leukemia (ALL), depending on clinical stage of the disease. At all stages of the disease, the patients developed T-cell immunodeficiency. A decrease in T lymphocyte scores and diminished CD4/CD8 ratio was associated with development of primary ALL attack. An increase in NK-cells was typical to ALL relapse. In general, ALL cell populations were characterized by a significant reduction of intracellular metabolic processes in lymphocytes. Chemiluminescent activity of neutrophil granulocytes changed in ALL patients with disease progression, being intensified at the stage of primary attack, followed be decreased activity during complete clinical remission and relapse, probably, due to depletion of internal reserves. The study confirmed that significant changes in ALL are associated with functional and metabolic state of lymphocytes and neutrophils upon progression of the disease, which is probably responsible both for development of complications, but it also may influence relapse risks and determine worse prognosis in general.